Commitment to Organization and Competency (Study on Caregivers in Daycare) - Hasanah, Viena Rusmiati; Heryanto, Nunu; Zanella, Selly; Saepudin, Asep; Jubaedah, Yoyoh (Universitas Negeri Semarang, 2019)
Daycare or Childcare is a very necessary place for women who work to provide parenting and education services to their children while they work. Caregiver Competence in providing services, parenting, is very important to learn. Based on the results of the study, the achievement of competency of an employee has a relationship with a commitment to an organization. This research aims to learn more about the commitment to the Organization with caregiver competence, especially in the competency that supports the development of early childhood. The assessments conducted in this study are quantitative by a descriptive method. This research was conducted at DayCare in Bandung. Respondents of this study supported 33 caregivers. The results of this study show that there are only three commitments for organizations that are partially related to the competency supporting child development, namely emotional problems and thinking skills, experience and biographic characteristics, and understanding and The values correspond to the category of caregivers with a fairly strong relationship category. The other two sub-variables are work motivation and organizational culture, not directly having a relationship with competency supporting child development. Furthermore, commitment to the organization, simultaneous support with competencies supporting child development belongs to the category is quite strong. This research proves how to care for early childhood must have adequate intelligence and thought with good values and adequate experience to demonstrate competence in supporting child development, in DayCare or ChildCare.